Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Pendidikan Kewarganegaraan dengan Metode Diskusi di Kelas VI SDN. No. 035/XI Larikkemahan Tahun 2016/2017 - Yenni Hustita (Universitas Batanghari Jambi, 2018)
This study is a classroom action research that conducted in two cycles and each cycle consists of four activities namely planning, implementation, observation, and reflection. This study aims to improve student learning outcomes by the method of discussion on the civic education subjects, especially about Government System in Republic of Indonesia. The study was conducted from July to November 2016. This study involved 10 students of sixth grade at SDN. No. 035/XI Larikkemahan, Hamparan Rawang Subdistrict, Sungai Penuh City, Jambi Province. The data was collected is data of learning outcomes collected through test and observation. The data was analyzed by using descriptive analysis and simple statistical test. The results showed that the discussion method successfully improve student learning outcomes. Before the action, students earned an average grade of 54,0. After the action, the average grade increased to 66,0 (Cycle I) and 76,0 (Cycle II). The percentage of students who were able to fulfill the minimum criteria also increased. Before the action, the percentage of students who were able to fulfill the minimum criteria is 30,0%. Once given the action, the percentage of students who are able to fulfill the minimum criteria increases to 60,0% (Cycle I) and 80,0% (Cycle II). Thus, the method of discussion can improve student learning outcomes on the subject of Citizenship Education, especially about Government System in Republic of Indonesia.